ANALISIS PENERIMAAN ORANG TUA TERHADAP ANAK AUTIS DI SEKOLAH SKH 1 KOTA SERANG - Rida Nurfallah; Yahdinil Firda Nadhirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to analyze parents' acceptance of autistic children at SKH 1 School in Serang City. Using a qualitative approach, data was obtained through interviews and observations of parents of autistic children. The results showed that parents' acceptance is influenced by various factors, such as education level, social support, and stigma in the community. Some parents experienced initial difficulties in accepting their child's condition, which impacted on their involvement in supporting their child's development at school and home. However, with education, training and mentoring by the school, parental acceptance can gradually increase. This study emphasizes the importance of the role of families and schools in creating an environment that supports autistic children to develop optimally.